2021
DOI: 10.1080/14626268.2021.1915339
|View full text |Cite
|
Sign up to set email alerts
|

CRUX: a creativity and user experience model

Abstract: The field of Virtual Reality has been developing at a steady pace, and VR is finding new uses as a support for creative tasks. The objective of this study is to propose a theoretical model describing the links between user experience and creativity. Pre-existing theoretical links have been identified in relevant scientific literature. Two experiments were then conducted in order to identify new links and replicate results. These experiments involved respectively 76 and 42 participants who individually performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The model itself linked to a method for predicting CS before its onset and was included as such. Creativity and User Experience Model (CRUX) [ 30 ] From the CRUX Model, the aspect of UX was taken as a possible method to reduce CS For example, if the VE was rigorously tested by means of tried and tested usability and UX methods, it should assist in reducing the effect of CS and stress, while increasing novelty, flow, and positive emotions. Structural Model: Relationship of Control, Cybersickness and Prescence [ 31 ] * This model was not named per the authors, and only referred to as a structural model From this Structural Model, various aspects such as the relationships between CS, presence and workload, were taken and added to the CyPVICS Framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model itself linked to a method for predicting CS before its onset and was included as such. Creativity and User Experience Model (CRUX) [ 30 ] From the CRUX Model, the aspect of UX was taken as a possible method to reduce CS For example, if the VE was rigorously tested by means of tried and tested usability and UX methods, it should assist in reducing the effect of CS and stress, while increasing novelty, flow, and positive emotions. Structural Model: Relationship of Control, Cybersickness and Prescence [ 31 ] * This model was not named per the authors, and only referred to as a structural model From this Structural Model, various aspects such as the relationships between CS, presence and workload, were taken and added to the CyPVICS Framework.…”
Section: Resultsmentioning
confidence: 99%
“…By conducting such tests, the developers can fix issues with the VE that might eventually induce CS; therefore, usability and UX were included in the CyPVICS Framework. The CRUX Model [ 30 ], along with other research [ 59 , 87 ], indicated that a VE with a good usability level and a good UX could assist in reducing CS symptoms. The CRUX model shows the links between aspects that affect user experience (UX) and aspects that affect creativity [ 30 ].…”
Section: Discussion: Cypvics Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…VR is also superior to pen and paper for creative sketching because it leads to a satisfying level of efficiency, effectiveness, ease of use and enjoyment [28] and because it generates more extension of solution space, enhancement of idea transformation and inducement to a more holistic design approach for idea generation [30]. More details have been provided on the determinants of creative performance in VR by [9]: It appears that the stimulating nature of the tool (linked to the novelty) is important, and that cybersickness, which is specific to VR, can hinder creative performance.…”
Section: Immersive Sketchingmentioning
confidence: 99%
“…It is an effective technique to support ideation across various industries (Gallagher, 2017). The pragmatic characteristics of the tools used for sketching, and their impact in terms of user experience, are important factors in the creative performance of individuals (Fleury et al, 2021b). For example, movement affects fluency and novelty, whereas emotions affect flexibility and originality.…”
Section: Introductionmentioning
confidence: 99%